If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + 70x = 875 Solving 35 + 70x = 875 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 70x = 875 + -35 Combine like terms: 35 + -35 = 0 0 + 70x = 875 + -35 70x = 875 + -35 Combine like terms: 875 + -35 = 840 70x = 840 Divide each side by '70'. x = 12 Simplifying x = 12
| x+3+x+4+x=76 | | 5-20x=12x-40 | | 5y-2x=7 | | Y=3x+24 | | 5(3-t)-(2-3t)=10 | | 5+x=3x-9 | | Ln(2x+9)=6 | | 4c-2(c-8)=4+3c | | 1/4-x=3x/5-2 | | y+3=x-5 | | 21/6p-1=6 | | 2t-5-6=3 | | 3(5x-7)=7x+7-6x | | 5-z=4+3z | | -2[3(2q+1)-5]+7=3(5-4q)+2 | | -5x-7/3=23/3 | | 1=x(.05) | | 5b=-125 | | 3-3=9x+5x | | 13-30/x=x | | 8x-6y=36 | | m+m+2m= | | -2=6-z-z | | 4=4-6n-3n | | 15X^2+14X=27X | | 19-a+4a=7 | | (2n+2)(6n+1)=0 | | -6=12-4/8t | | 3(2)(4)-12/6(3)= | | (-3)(-5m)= | | 3(2)(4)-12*6= | | 3(2)(4)-12= |